2014
DOI: 10.1016/j.devcel.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

NRP1 Presented in trans to the Endothelium Arrests VEGFR2 Endocytosis, Preventing Angiogenic Signaling and Tumor Initiation

Abstract: Neuropilin 1 (NRP1) modulates angiogenesis by binding vascular endothelial growth factor (VEGF) and its receptor, VEGFR2. We examined the consequences when VEGFR2 and NRP1 were expressed on the same cell (cis) or on different cells (trans). In cis, VEGF induced rapid VEGFR2/NRP1 complex formation and internalization. In trans, complex formation was delayed and phosphorylation of phospholipase Cγ (PLCγ) and extracellular regulated kinase 2 (ERK2) was prolonged, whereas ERK1 phosphorylation was reduced. Trans co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
80
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 41 publications
10
80
0
Order By: Relevance
“…However, it seems that these classic models might not effectively capture the full complexity of the VEGF system. Recently, new data have surfaced indicating that the role of co-receptors within the VEGF system is dependent on cellular context (30,31). Thus, the goal of the present study was to identify potential mechanistic elements for how co-receptors influence VEGF activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it seems that these classic models might not effectively capture the full complexity of the VEGF system. Recently, new data have surfaced indicating that the role of co-receptors within the VEGF system is dependent on cellular context (30,31). Thus, the goal of the present study was to identify potential mechanistic elements for how co-receptors influence VEGF activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mice expressing a VEGF isoform unable to bind NRP-1 die before postnatal day 14 because of bleeding in multiple organs or cardiac failure (26 -29), further reinforcing the notion that NRP-1-VEGF 165 interactions are essential for vascular development. Additionally, recent reports suggest that expression of these co-receptors on adjacent cells (trans) as opposed to cis (same cell) with respect to VEGFR-2 on endothelial cells leads to significant changes in signal transduction upon VEGF 165 binding (30,31).…”
mentioning
confidence: 99%
“…This might be different when PDGFRβ and NRP1 interact in trans, between two adjacent cells or even two different cell types. In the trans situation, physical hindrance would prevent internalization of both PDGFRβ and NRP1 and would lock them at the cell surface, possibly changing signaling kinetics from fast and transient to slow and persistent, as was recently shown for VEGFR2 signaling when NRP1 is presented in trans (Koch et al, 2014). Such a scenario would result in a spatially restricted change of PDGFRβ downstream signaling in a PDGF-D-specific manner.…”
Section: Pdgf-d Induces the Interaction Of Pdgfrβ And Nrp1 In Trans Bmentioning
confidence: 99%
“…It was first reported that Nrp expressed on CD45 ϩ hematopoietic cells enhances endothelial expressed VEGFR-2 activation, increasing endothelial cell proliferation and angiogenesis (78). More recently, a dramatic difference was shown for Nrp1 interactions with VEGFR-2 in trans (79). In trans, Nrp1 was found to limit receptor internalization and inhibit signal initiation and vascularization.…”
Section: Nrp Function In Cis and In Transmentioning
confidence: 99%